2003
DOI: 10.1034/j.1600-0528.2003.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of self‐reported tooth loss in a representative sample of Norwegian adults

Abstract: The annual incidence rate of tooth loss among Norwegian adults was found to lie within the range reported from other industrialized countries. After controlling for socio-demographic variables and the number of teeth present, the only borderline significant predictor of the incidence of tooth loss was the level of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
49
1
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 31 publications
7
49
1
15
Order By: Relevance
“…The decreased tooth loss in adolescents and adults observed over the last ten years indicates, possibly, a combination of the cohort effect, improvements in socioeconomic conditions, especially in education, 16 and in the health care system with the fl uoridation of tap water and widespread use of fl uoridated toothpastes. In the 1980s and 90s these two measures achieved broad coverage of the population and largely explain the reduction in the prevalence of dental caries, the principal cause of tooth loss, in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased tooth loss in adolescents and adults observed over the last ten years indicates, possibly, a combination of the cohort effect, improvements in socioeconomic conditions, especially in education, 16 and in the health care system with the fl uoridation of tap water and widespread use of fl uoridated toothpastes. In the 1980s and 90s these two measures achieved broad coverage of the population and largely explain the reduction in the prevalence of dental caries, the principal cause of tooth loss, in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 Epidemiological studies show that tooth loss constitutes a marker of social inequality in diverse societies; population groups at the bottom of the socioeconomic hierarchy have higher rates of tooth loss than those situated at the top of the scale. 3,6,7,15,16 In Brazil, the national oral health survey in 1986 revealed that, for adolescents (aged [15][16][17][18][19]) the mean number of teeth lost was 1.9, representing 15.2% of the DMFT (decayed, missing and fi lled teeth) index. For adults aged 35-44, the rate was 14.9 (66.5%) and it was 23.4 (86%) of the index for individuals aged between 50 and 59.…”
mentioning
confidence: 99%
“…Epidemiological studies have used a much lower percentage of the population as representative and have drawn conclusions about the population as a whole from their data. [18][19][20][21][22] While this survey may prove useful in demonstrating general trends in the beliefs and activity of GDPs in regards to periodontal disease, there are some limitations in the interpretation of data from this type of study. While subjects were randomly selected in an attempt to gain a representative sample of GDPs, bias may have been introduced with a return rate of 51.8 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is agreeable with earlier authors. 7,8,9,10 However, multiple logistic analyses showed only age and sex were found to be significantly associated with edentulism. As reported by other studies, age is strongly associated with edentulism.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%
“…9,21 Edentulism is closely associated with socioeconomic variables. [7][8][9][10]18 Women who were older, had no formal education, and were unemployed were more likely to be edentulous. Thus, oral health disparities may be due to differences in health literacy and behaviors, attitudes towards oral health, as well as dental care and access and use of dental services and types of treatment available.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%